2016
DOI: 10.1037/neu0000314
|View full text |Cite
|
Sign up to set email alerts
|

Slow wave and REM sleep deprivation effects on explicit and implicit memory during sleep.

Abstract: These findings demonstrate the importance of measuring the sleep cycles throughout the entire night, and the contribution of both SWS and REM sleep to memory consolidation. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 105 publications
4
17
0
Order By: Relevance
“…However, no study to date examined whether these basic research findings also apply in the context of traumatic memories. Our results show several correspondences with basic research: In line with findings from Giganti et al (2014) and Casey et al (2016), we found that explicitbut not implicit -'trauma' memory was higher after sleep than after partial sleep deprivation. Moreover, group differences were selectively evident for recollection-based recognition memory, which is in agreement with previous findings from Drosopoulos et al (2005) and others (Atienza & Cantero, 2008;Daurat et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, no study to date examined whether these basic research findings also apply in the context of traumatic memories. Our results show several correspondences with basic research: In line with findings from Giganti et al (2014) and Casey et al (2016), we found that explicitbut not implicit -'trauma' memory was higher after sleep than after partial sleep deprivation. Moreover, group differences were selectively evident for recollection-based recognition memory, which is in agreement with previous findings from Drosopoulos et al (2005) and others (Atienza & Cantero, 2008;Daurat et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…In line with the aforementioned studies, we predicted that recollection-based recognition memory would be higher in the Sleep group (Atienza & Cantero, 2008;Daurat et al, 2007;Drosopoulos et al, 2005). Moreover, we hypothesized that the Sleep group would show similar priming effects as the Partial sleep deprivation group (Casey et al, 2016;Giganti et al, 2014). Finally, we predicted that the Sleep group would experience fewer intrusions than the partial sleep deprivation (PSD) group (Kleim et al, 2016;Woud et al, 2018).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…This result adds to a growing literature linking sleep with declarative knowledge acquisition, including word learning (1,24,25). In the TD group only, 4-h retention of the object-label association correlated with increased time in REM, consistent with previous studies indicating a role of REM sleep in the consolidation of languagerelated learning (17,21,25). Our results indicate that REM is also important for active consolidation of new arbitrary labels.…”
Section: Discussionsupporting
confidence: 90%
“…What physiological processes allow the sleep experienced while napping to be beneficial? Both rapid eye movement (REM) and non-REM (NREM) stages of sleep contribute to the consolidation of nascent material (7,(16)(17)(18). NREM 3 (N3, slow wave) sleep orchestrates hippocampal-neocortical dialogue and information transfer (19,20).…”
mentioning
confidence: 99%